GERAKAN AMAL TROUPE PADA RELAWAN (SR) SEDEKAH ROMBONGAN - Dhaniar Ratih Rahmawati; Muhammad Nur (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
This research is about philanthropic practices conducted by volunteers (SR) Alms Group, one of the charitable organizations engaged in social care. This organization is based on organizations related to Muslim religions, this organization is intended to bring together donors without a neat organizational system and has only less than ten members involved and moves reactively on the road, but the structure of rational transitions is fast. The study was conducted field observations with interviews with SR volunteers who were in Yogyakarta, the authors wanted to know the motives for encouraging volunteers to work in SR charities, and also wanted to find out how to improve the performance of SRs through either instrumental or reactive or spontaneity. The results of this study prove that SR volunteers Get inspiration from their religious ethos that motivates them to work with charity motorcycles in SR, and have a perspective related to others will be transactional, have reciprocity for those who own it. While spontaneous work actions are their way of not making it difficult for people who need help helping is action and also by working through instrumental action because the intended purpose is to eradicate the poor who are oppressed due to economic, health factors, all of which cannot be done through spontaneous giving .